HIP 7: USING A BUNDLE OF CARE TO STREAMLINE THE MANAGEMENT OF PATIENTS WITH A FRACTURED NECK OF FEMUR. Issue 9 (14th August 2014) - Kerr, Jacques; Bishop, Mary; Meikle, Alastair; Lakie, Kirk; Davidson, Jane
Abstract : Objectives & Background: SIGN guideline 111 makes recommendations on the optimal management of patients with a hip fracture. 1 It is clear from the use of care bundles in other conditions, eg sepsis, that these perform very well in time-critical settings and ensure that all necessary actions for person-centred care are achieved timeously. Given the success of our Emergency Department (ED) compliance with the Sepsis 6 bundle (100%–unpublished data) the principal author (JK) rationalised that a bundle applied to the SIGN hip fracture recommendations would ensure that all actions were achieved in a timely manner. Methods: We used an improvement methodology strategy to devise a bundle of care for patients with a fractured neck of femur. This work culminated in a list of 7 actions that could be captured in an acronym devised by the principal author as an aide-memoir (see table 1). The principal author ran training sessions on the bundle with all ED medical and nursing staff and data were captured over a four-month period (October 2013–February 2014) to examine compliance and to compare with data from the same period in the previous year. All actions in the bundle had to be achieved within the hour.Table 1 Results: Analysis of data from the study period showed a significant improvement in compliance with a) intravenous fluid therapy administration: 37% pre- and 91.4% post-bundle; b) opiates and regional nerve block administration: 35% pre- and 75% post-bundle; c) documentation of SIRS score: 40% pre- and 91% post-bundle, and d) inspection of pressure areas: 5% pre- and 100% post-bundle. Conclusion: Although fractures of the neck of femur do not necessarily result in the physiological derangement associated with sepsis, it is evident that the use of a bundle of care will ensure that hip fracture patients are managed in a timely, person-centred and safe fashion as recommended in SIGN 111. Future work will concentrate on improving compliance with all seven actions within one hour of patient attendance.